Pendampingan Legalitas Berbasis Online Single Submission Risk-Based Approach (OSS RBA) dalam Membuka Akses Permodalan dan Memperkuat Legalitas Usaha UMKM di Kelurahan Batu Besar. - H. Muhammad Sapuan; Septa Diana Nabella; Indirah Tri Patikasari; May Sarah Amril; Lian Natalia Angria Sari; Icha Hana Cahya; Rica Fitri Susanti UE; Mohamad Hisam (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2026)
Micro, small, and medium enterprises (MSMEs) in Batu Besar Village, Nongsa District, Batam City, remain largely unregistered despite operating near a strategic economic zone bordering an international airport, industrial estates, and the Nongsa tourism corridor. This legal gap restricts their access to formal financing, government support programs, and legal protection in business disputes. This community assistance program addressed the problem by facilitating Business Identification Number (Nomor Induk Berusaha/NIB) registration through Indonesia’s Online Single Submission Risk-Based Approach (OSS RBA) system, in accordance with Government Regulation No. 28 of 2025. The program combined participatory qualitative and quantitative methods, comprising outreach, baseline profiling, face-to-face technical registration assistance, and document handover, implemented over one month. Of 38 targeted business owners, all of whom (100%) lacked an NIB at baseline, 35 (92.1%) successfully obtained registration between 18 June and 1 July 2026; culinary businesses were the dominant sector (15 businesses, 39.5%), and most owners reported monthly revenue of IDR 1-5 million (45%). The results confirm that MSME informality in this setting is largely a technical-administrative barrier that structured, face-to-face assistance can resolve within a short period. Legal registration opens formal pathways for these MSMEs to access financing, join the free halal certification program (SEHATI), and pursue partnerships with the hotel and resort sector in Nongsa, strengthening the resilience of micro-enterprises in this strategic economic area.